2016
DOI: 10.1128/mcb.01003-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effects of Hypomorphic Thoc1 Alleles on Embryonic Development in Rb1 Null Mice

Abstract: The Rb1 tumor suppressor protein is a molecular adaptor that physically links transcription factors like E2f with various proteins acting on DNA or RNA to repress gene expression. Loss of Rb1 liberates E2f to activate the expression of genes mediating resulting phenotypes. Most Rb1 binding proteins, including E2f, interact through carboxyl-terminal protein interaction domains, but genetic evidence suggests that an amino-terminal protein interaction domain is also important. One protein that binds Rb1 through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Therefore, these tumors could be selectively sensitive to agents that target these processes (e.g., proteasome inhibition or unfolded protein stress). This concept has been tested in limited contexts evaluating either genetic interactions (e.g., between RB1 deletion and targeting RNA processing) 47 or drug sensitivities specific to RB-deficient tumors 48 . Conversely, we identify a host of processes that would appear to be more engaged in indolent tumors or those that have forced out of the cell cycle therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these tumors could be selectively sensitive to agents that target these processes (e.g., proteasome inhibition or unfolded protein stress). This concept has been tested in limited contexts evaluating either genetic interactions (e.g., between RB1 deletion and targeting RNA processing) 47 or drug sensitivities specific to RB-deficient tumors 48 . Conversely, we identify a host of processes that would appear to be more engaged in indolent tumors or those that have forced out of the cell cycle therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…The human protein THO complex 1 (THOC1) was originally identi ed as a nuclear matrix component that binds to the tumor suppressor retinoblastoma (RB) protein [40,41]. Recent research found that high levels of THOC1 were associated with tumor size and aggressiveness in breast and lung cancer cells, and that down-regulation of THOC1 was essential for the NO-mediated cytotoxicity induced by CCL-34 in cancer cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…The human protein THO complex 1 (THOC1) was originally identified as a nuclear matrix component that binds to the tumor suppressor retinoblastoma (RB) protein [36,37]. Recent research found that high levels of THOC1 were associated with tumor size and aggressiveness in breast and lung cancer cells, and that down-regulation of THOC1 was essential for the NO-mediated cytotoxicity induced by CCL-34 in cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%